VYGOTSKY’S THEORY IN THE DEVELOPMENT OF SOCIAL AND COGNITIVE SKILLS OF THE ALPHA GENERATION - Malik, Muh Syauqi; Maslahah, Maslahah; Maulida, Arina Zulva; Nikmah, Lutfiyatun; Hashinuddin, Ahmad (FASHLUNA, 2025)
Quality education is a global challenge, especially for Generation Alpha, which faces difficulties in social and cognitive skills due to a lack of direct interaction. To address this problem, this study proposes modeling learning methods based on Vygotsky’s theory that emphasizes structured social interaction and the use of technology as learning aids. This method involves an in-depth analysis of more than 20 relevant Scopus-indexed journals, with a qualitative approach that emphasizes document analysis techniques and thematic analysis to identify emerging themes and patterns. The novelty value of this research lies in the application of Vygotsky’s theory in the context of modern education, which has not been explored much, as well as the emphasis on collaboration and group discussion as an effective learning method. The results show that the application of Vygotsky’s principles, such as social interaction and emotional experience, can improve the social and cognitive skills of Generation Alpha, as well as support better academic achievement. As such, this research makes a significant contribution to educational literature and offers practical recommendations for educators and policymakers to create more effective and meaningful learning environments.